ANALISIS HUKUM ISLAM TERHADAP STRATEGI PROMOSI SISTEM PERSUADE PADA PEMBELIAN SEPEDA MOTOR SECARA KREDIT DI UD. YAMAHA RAYA MOJOKERTO - Maya Nurmalinda (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2015)
In the current era, the ease of having motorcycle vehicle has can be felt consumers. Proved only by providing a relatively low down payment in the purchase of consumer credit may have a motorcycle they want, even though the credit system of money that they will pay on the installment greatly exceeds the predetermined price. Here not a few practices more direct dealers consumers to buy a motorcycle just to give the option purchases on credit. While the consumer is able to buy a motorcycle in cash. One of them at the dealer UD. Yamaha Raya Mojokerto, have taken advantage of promotional strategies persuade the system to direct and persuade consumers to buy a motorcycle on credit in accordance with the wishes of the marketing dealers. By using this system the dealer to inform and remind consumers about the advantages eight motorcycle purchase on credit regardless of financial ability and willingness of consumers. From these studies if it is associated with a review of Islamic law, a system implemented persuade UD. Yamaha Raya characterized by elements of persuading, encouraging, influencing consumers to buy on credit, show transactions that are prohibited by Islam. Due to what has been done by the dealer marketing, solely in order to obtain greater profits, which are not directly harm consumers.